The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/19476337.2017.1343866
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and free radical scavenging properties ofZea maysfemale inflorescences (maize silks) from Mexican maize landraces

Abstract: Maize silks are used worldwide as a natural-based treatment for various illnesses. The biological activity of maize silks is mainly attributed to their content of polysaccharides and polyphenols. Therefore, it is worthwhile the identification of maize varieties or races that accumulate large amounts of these compounds in their staminate flowers. In the present study, the compositional and antioxidant properties of silks from three maize races (Cónico, Gordo and Cristalino) natives to Mexico were investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Meanwhile, a lower molecular weight (385 kDa) has been reported by Mendoza‐López et al . (2018). The monosaccharide composition of CSP was identified utilising HPLC analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a lower molecular weight (385 kDa) has been reported by Mendoza‐López et al . (2018). The monosaccharide composition of CSP was identified utilising HPLC analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular weight of CSP was 2846 kDa (as analysed by LC-20A HPLC), which is lower than that reported byChen et al (2014) who obtained lower molecular weight distribution (10.52 × 10 4 and 6.88 × 10 4 Da) from CSP by enzymolysis-ultrasonic-assisted extraction. Meanwhile, a lower molecular weight (385 kDa) has been reported byMendoza-L ópez et al (2018). The monosaccharide composition of CSP was identified utilising HPLC analysis.…”
mentioning
confidence: 99%
“…Flavonoids are the main bioactive compounds in pigmented corn silk [35] as shown in Table 9. Some authors reports until 3644.9 mg/100 g in Serbian purple corn and Mexican pigmented corn reports 797.1 a 2602.4 mg/100 g [61]. Among the flavonoids identified and quantified in pigmented corn silk is the maysin with 12.6-17.1 mg/100 g [35], quercetin (1.58 mg/100 g) and narigenin glucoside (6.45 mg/100) [21].…”
Section: Flavonoids In Pigmented Corn Silkmentioning
confidence: 99%
“…Due to its potential benefits, several in vitro and in vivo studies have reported its biological activities. These activities include antioxidant, , anti-inflammatory, , hyperglycemia reduction, antifatigue, , antidepressant, antihyperlipidemic, antidiabetic, , and antiobesity activity . It also showed protection against radiation and nephrotoxicity. , Therefore, this assignment was developed to serve as a meaningful hands-on exercise to introduce undergraduate Chemistry students to a common procedure in the early phase of drug discovery using corn silk.…”
Section: Introductionmentioning
confidence: 99%